Equality Rights - Chuamchim, Nadtathida; Phuengpha , Noppawan (Universitas Muhammadiyah Sidoarjo, 2024)
Equality rights are fundamental to human dignity, ensuring that all individuals, regardless of gender, race, or sexuality, receive equal treatment under the law. In today's hyperconnected world, where diverse identities and communities interact more frequently through digital means, the struggle for equality—especially in terms of marriage rights for people of diverse sexualities—remains significant. While some countries have embraced equal marriage, others continue to uphold traditional views, denying certain groups their basic human rights. This journal explores the evolution of equal marriage rights as a reflection of broader human rights developments. It examines the principle that all human beings are born equal and deserve the right to marry whomever they choose, free from discrimination. Using a qualitative analysis, we investigate case studies from countries that have passed equal marriage laws and compare them to nations where such laws are still absent. By analyzing the underlying social and political factors contributing to the advancement or hindrance of these rights, this paper aims to highlight the importance of equal marriage in achieving human equality in a globalized, interconnected world.